Confidentiality and protection of official records in the freedom of information era: Nigeria’s situation (2010)
Records of great value are generated daily in the public sector in the course of carrying out the affairs of the state. These records document the activities of the government and much of the information they contain is crucial for decision making. The information may, however, also be of strategic value or sensitive nature such that unrestricted access to them may be inimical to national or personal interests. This paper examines the specific provisions in existing laws and public service rules in Nigeria which restrict access to public records and information in Nigeria. It reviews the provisions in terms of the need to protect the privacy of individuals and safeguard national security and interests. It also examines potential areas of conflict between these restrictive provisions and some of the provisions of the Freedom of Information (FOI) Bill which the country is seeking to pass into law. The paper highlights the importance of striking a right balance between the need to promote access to public records in the interest of open and responsible government through FOI legislation and the equally important need to restrict access to such records and information in order to protect national strategic security and interests.